Genetics of Spontaneous Intracerebral Hemorrhage: Risk and Outcome - Guo, Hongxiu; You, Mingfeng; Wu, Jiehong; Chen, Anqi; Wan, Yan; Gu, Xinmei; Tan, Senwei; Xu, Yating; He, Quanwei; Hu, Bo (Frontiers in Neuroscience, 2022)
Spontaneous intracerebral hemorrhage (ICH) is a common fatal event without an effective therapy. Of note, some familial aggregation and inherited tendency is found in ICH and heritability estimates indicate that genetic variations contribute substantially to ICH risk and outcome. Thus, identification of genetic variants that affect the occurrence and outcome may be helpful for ICH prevention and therapy. There are several reviews summarizing numerous genetic variants associated with the occurrence of ICH before, but genetic variants contributing to location distribution and outcome have rarely been introduced. Here, we summarize the current knowledge of genetic variants and pay special attention to location distribution and outcome. So far, investigations have reveled variations in APOE, GPX1, CR1, ITGAV, PRKCH, and 12q21.1 are associated with lobar ICH (LICH), while ACE, COL4A2, 1q22, TIMP1, TIMP2, MMP2, MMP9, and TNF are associated with deep ICH (DICH). Moreover, variations in APOE, VWF, 17p12, HP, CFH, IL6ST, and COL4A1 are possible genetic contributors to ICH outcome. Furthermore, the prospects for ICH related genetic studies from the bench to the bed were discussed.